GLOBALIZATION AND IMPLICATIONS FOR THE SOCIAL SYSTEM - kakepoto, Hamadullah (Journal of Research in Humanities, 2023)
Globalization has been conceptualized in the Western world-view. It impacts seriously on the social system. This essay discusses basic manifestations of globalization; likely goals of globalization; and considers its salient implications for the social system. With regards to likely goals of globalization, it seems the establishment of a world government at some later date is one of the likely targets of globalization. Global inequality and global social conflict scenario are the two basic issues of globalization. Social systems worldwide face serious challenges of globalization.